'Culturespeak' is everywhere: an analysis of culturalist narratives in approaches to sexuality education in Mozambique. Issue 2 (3rd April 2019) - Miedema, Esther
ABSTRACT: Building on postcolonial feminist scholars and critical anthropological work, this paper analyses the frequent deployment of the notion of 'culture' by decision-makers, educators, international agency staff and young people in the design, delivery and uptake of sexuality and HIV prevention education in Mozambique. The paper presents qualitative data gathered in Maputo, Mozambique to highlight the essentialising nature of culturalist assumptions underpinning in-school sexuality education. I argue that conceptions of 'traditional' and 'modern' culture are deployed to explain the epidemic, both of which spectacularise and decontextualise phenomena and practices, and perpetuate the western trope of the Third World Woman. The paper concludes by arguing that a singular emphasis on 'culture' – in its various guises – diverts attention from structural causes of young Mozambican women and men's vulnerability to HIV and AIDS, and crucially, rather than problematise gender relationships, reifies and solidifies these. Thus, while sexuality and HIV prevention education cannot be understood or delivered independently of the cultural context in which it is situated, a more nuanced conception of culture is required – that is, one that is attentive to questions of power and specifically, who is in a position to make meanings 'stick'.